Learning Profile of Students with Intellectual Disabilities through the E-LAPD Live Worksheet on Chemical Reactions Material - Jihan Sakinah Al Farhani; Soekarmiani; Rahmania Fitrah Sari; Ima Kurrotun Ainin; Dian Novita (Postgraduate, University of Mataram, 2025)
Students with intellectual disabilities experience difficulties in understanding abstract concepts such as chemical equations and reaction balancing. This study aims to describe the learning profile and determine the learning outcomes of students with intellectual disabilities using E-LAPD based on Liveworksheet integrated with the Individualized Education Program (IEP). This research employed a mixed methods approach with an embedded design. Quantitative data were obtained from pre-test and post-test to measure the improvement in learning outcomes, while qualitative data were collected through students’ interviews after completing the E-LAPD using N-Vivo 11 to identify responses and challenges during the learning process. The research subjects consisted of three students with intellectual disabilities at SMAN 10 Surabaya. The results revealed that students experienced difficulties in understanding chemical symbols, connecting reactants and products, and balancing equations independently. The implementation of E-LAPD based on Liveworksheet, which provides visual support, step-by-step guidance, and interactive exercises, helped students better understand the process of reaction balancing. An improvement in learning outcomes was demonstrated by higher post-test scores in all subjects. In conclusion, the E-LAPD based on Liveworksheet has promising potential as an adaptive learning medium for students with intellectual disabilities, although further development is required regarding content refinement and learning assistance strategies.